Literasi Pemasaran Digital dan Teknologi Keuangan Sebagai Sarana Peningkatan Omset UMKM di Probolinggo - Maria Febri Puji Hartanti; Candra Nola Mardita; Michael Tirta; Antonius Rama Angga Putra; Idfi Setyaningrum (Universitas Batanghari, 2023)
The MSME sector plays an important role in national economic growth. The recovery adaptation period brings new opportunities for the MSME sector to develop and improve. By educating businesses about financial literacy, financial technology can help MSMEs grow financially. This business development method is especially seen in financial technology financing. In addition, careful use of access to finance should be encouraged among MSMEs to avoid financing problems. Quantitative and qualitative approaches are carried out to understand MSME financial literacy. The triangulation model combines in-depth interviews and observations of MSMEs to combine the strengths of both qualitative and quantitative approaches. This method is used to assess the financial needs of MSMEs using literature review, data collected from other sources and previous research journals. In addition to funding funding, Fintech can support the needs of MSMEs by combining various financial tools and services. In this new adaptation period, MSMEs need financial literacy and access to Fintech in order to develop. This is because many of them need to manage their finances wisely in order to remain financially capable. After COVID-19 researchers surveyed MSMEs in Probolinggo City for this study. The findings from this study indicate that digital marketing and financial technology payment services have a significant positive effect on increasing sales of Small, Micro, and Medium Enterprises (MSMEs). This is shown by the fact that fintech has a significant positive influence on increasing MSME turnover. In addition, digital literacy has a small but significant effect in reducing the negative impact of fintech on MSME sales. Observing the findings and benefits of the MSME study is expected to help improve MSME digitalization and the financial literacy of MSME entrepreneurs. Because technology plays an important role in business activities and it is important for entrepreneurs to increase their digital literacy in the current era.